The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/agronomy9060287
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Three Quinoa Cultivars (Chenopodium quinoa Willd.) to Salinity and Alkalinity Stress During Germination Stage

Abstract: Salinity and alkalinity are two of the main causes for productivity losses in agriculture. Quinoa represents a better alternative for global food products such as rice and wheat flour due to its high nutritional value and abiotic stress tolerance. Three cultivars of quinoa seeds (Titicaca, Puno and Vikinga) originating from Denmark were used in the experiments. The seeds were germinated under the action of three different salts (NaCl, Na2SO4, Na2CO3) at 0–300 mM for five days and the germination rate was calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
(56 reference statements)
5
11
1
Order By: Relevance
“…Corresponding reductions in germination varied from a high of 80% to a low of 31% relative to the control across all genotypes (Table 3). Our results concur with previous studies, which also reported significant reductions in quinoa seed germination with increasing salinity (Gómez-Pando et al, 2010;Panuccio et al, 2014;Stoleru et al, 2019). For example, Gómez-Pando et al ( 2010) found that seed germination was drastically reduced at 300-mM (∼30 dS m −1 ) NaCl concentration when 182 Peruvian accessions were tested for their salinity tolerance at germination stage.…”
Section: Percent Germination and Stisupporting
confidence: 93%
“…Corresponding reductions in germination varied from a high of 80% to a low of 31% relative to the control across all genotypes (Table 3). Our results concur with previous studies, which also reported significant reductions in quinoa seed germination with increasing salinity (Gómez-Pando et al, 2010;Panuccio et al, 2014;Stoleru et al, 2019). For example, Gómez-Pando et al ( 2010) found that seed germination was drastically reduced at 300-mM (∼30 dS m −1 ) NaCl concentration when 182 Peruvian accessions were tested for their salinity tolerance at germination stage.…”
Section: Percent Germination and Stisupporting
confidence: 93%
“…Similar findings were observed by [9] in the groundnut. S 0 Control 0 mM NaCl recorded 87.85% Similar findings were observed by [10] in puno cultivar of Quinoa and the lowest readings were recorded in S 2 200Mm NaCl is 82.27%. The maximum germination % with interaction treatments and salinity (T×S) was recorded with T 9 S 0 -Beejamrutha100% at 0mM NaCl is 92% and also other quality parameters recorded highest in Beejamrutha 100% compared with other treatments and control.…”
Section: %supporting
confidence: 79%
“…In addition, Rosa, Hilal, Gonzalez, and Prado (2009) found that quinoa is able to maintain Ca 2+ /Na + and K + /Na + selectivity under saline stress. These evidences suggest that quinoa can be a good candidate for cropping system under soil salinization and for salinity tolerance studies (Stoleru et al, 2019).…”
Section: Introductionmentioning
confidence: 94%